2012
DOI: 10.1146/annurev-cellbio-092910-154010
|View full text |Cite
|
Sign up to set email alerts
|

Driving the Cell Cycle Through Metabolism

Abstract: For unicellular organisms, the decision to enter the cell cycle can be viewed most fundamentally as a metabolic problem. A cell must assess its nutritional and metabolic status to ensure it can synthesize sufficient biomass to produce a new daughter cell. The cell must then direct the appropriate metabolic outputs to ensure completion of the division process. Herein, we discuss the changes in metabolism that accompany entry to, and exit from, the cell cycle for the unicellular eukaryote Saccharomyces cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
116
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 183 publications
(184 reference statements)
3
116
1
3
Order By: Relevance
“…In an environment that contains a mixture of sugars, such as glucose and galactose, microbial cells regulate their response according to a carbon hierarchy mediated by catabolite repression. Galactose metabolic genes (GAL genes) are induced to a significant degree only after glucose-based catabolite repression is relieved, resulting in a lag in growth at the point of glucose exhaustion while GAL pathway proteins are produced (1)(2)(3)(4)(5)(6). Recent studies of sugar integration in bacteria (7,8) suggested that in these organisms the combinatorial response results from the multiplication of individual responses to different sugars.…”
mentioning
confidence: 99%
“…In an environment that contains a mixture of sugars, such as glucose and galactose, microbial cells regulate their response according to a carbon hierarchy mediated by catabolite repression. Galactose metabolic genes (GAL genes) are induced to a significant degree only after glucose-based catabolite repression is relieved, resulting in a lag in growth at the point of glucose exhaustion while GAL pathway proteins are produced (1)(2)(3)(4)(5)(6). Recent studies of sugar integration in bacteria (7,8) suggested that in these organisms the combinatorial response results from the multiplication of individual responses to different sugars.…”
mentioning
confidence: 99%
“…Cai and Tu (2012) noted changes in metabolism that resulted from cell cycle progression and noted that metabolites may play a key role in the regulation of entry into the S-phase. The paper Newcomb, Diderich, Slattery, and Heideman (2003) found a possible link between the rate of glycolysis and gene expression that is important for the initiation of the S phase.…”
Section: Introductionmentioning
confidence: 99%
“…Notons que certaines bactéries à croissance rapide initient un nouveau cycle de réplication d'ADN avant même d'avoir achevé le précédent, menant à un cycle cellulaire où la phase B (ou G1) disparaît. Bien qu'ayant des fonctions différentes, le métabolisme et le cycle cellulaire doivent nécessairement communiquer [1]. En effet, une cellule n'entamera pas une étape du cycle cellulaire qui est « éner-givore » si son état métabolique ne le lui permet pas, par exemple en conditions de carences nutritives.…”
unclassified
“…En effet, une cellule n'entamera pas une étape du cycle cellulaire qui est « éner-givore » si son état métabolique ne le lui permet pas, par exemple en conditions de carences nutritives. De même, il serait délétère pour une cellule, en phase S, de catalyser des réactions métaboliques généra-trices de dérivés réactifs de l'oxygène (ROS), par exemple les réactions de la chaîne de transport d'électrons en vue de produire de l'énergie, Le métabolisme peut être défini comme l'ensemble des transformations (bio-) chimiques se produisant au sein d'une cellule qui lui permettent de se maintenir en vie, de se développer et de se reproduire 1 . Ces réactions servent, d'une part, à extraire l'énergie des nutriments (on parlera alors de catabolisme) et, d'autre part, à synthétiser l'ensemble des « briques de la vie » nécessaires au fonctionnement de la cellule (on parlera dès lors d'anabolisme).…”
unclassified
See 1 more Smart Citation